Karyotypes of Akodon orophilus Osgood 1913 and Thomasomys sp. (Rodentia: Sigmodontinae) from Huánuco, Peru - Pacheco, Víctor (2012)
Conventional chromosomal preparations were made of three native mice from Huánuco, Peru: a male and a female of Thomasomys sp., and a male of Akodon orophilus. Thomasomys sp. had a karyotype of 2n = 42, XY (n = 21), meanwhile A. orophilus presented 2n = 22, XY (n = 11). Comparisons between chromosomal pairs from the existent literature indicate that both are new karyotypes. Thomasomys sp. has a distinct sexual Y chromosome, the only metacentric (m) reported for the genus. The chromosomes X and Y of A. orophilus are acrocentrics (a); and the length of chromosome Y (2/3 of the length of X) distinguishes A. orophilus from other congeneric. Because the structural differences between the sexual chromosomes usually generates mechanism of reproductive isolation at intraspecific level and are bigger still in interspecific crosses, we concluded that the karyotypes reported here support the validity of the species A. orophilus and suggest that Thomasomys sp. represents a new species to science.